Etika Wahhabian dan Etika Protestan - Bahtiar, Riza (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2017)
This paper effort to define the theology of Wahhabian which is divided into three, such as: tauhid rububiyah, tauhid asthma, and the nature and monotheism of worship, wahhabian ethos in general, followed by wahhabian ethics divided into five points, namely 1)